Evaluation of native rhizobacteria as promoters of plant growth for increased yield in lentil (Lens culinaris) - Saini, Preeti; Khanna, Veena (Recent Research in Science and Technology, 2012)
Six rhizobacterial isolates obtained from lentil rhizospheric soils were characterized and found belonging to genera Bacillus and Pseudomonas. The isolates were evaluated for their plant growth and antagonistic traits. Maximum catechol-type siderophore was produced by B-40 (97μg/ml) and hydroxamate-type siderophore by B-20 (129.5μg/ml). A wide variation in the phosphate-solubilizing efficiency (7.1-34.4 mg/100ml) was observed. Further, all these isolates were able to secrete phytohormone Indole-acetic-acid which ranged from 12.7-106.1μg/ml. On the basis of their PGP traits B-40 and P-1 were selected for field studies. Field experiments were carried out in order to test the effect of dual inoculations (selected PGPRs and Rhizobium sp. along with check strain KB-133) on lentil growth. The system productivity was highest in case of dual inoculations of PGPRs with Rhizobium. The grain yield with dual inoculations of Rhizobium with B-40 (1703 kg/ha) and P-1 (1679 kg/ha) was statistically on par to dual inoculation with KB-133 (1698 kg/ha). These data suggest that B-40 and P-1 can act synergistically with R. leguminosarum in promoting lentil growth.